Efektifitas Akupresure dalam Menurunkan Skala Nyeri Pasien Hipertensi Diwilayah Kerja Puskesmas Perumnas - Sri Haryani; Misniarti Misniarti (JURNAL KEPERAWATAN RAFLESIA, 2020)
Acupressure is a non-pharmacological therapy that can be used to reduce blood pressure in hypertensive patients and can be included in the nursing care plan. Hypertension in Indonesia is 44.1% and the mortality rate due to hypertension is 34.1%. Hypertension data in Perumnas Public Health Center are 790 cases. This study aimed to determine the effect of acupressure on pain scales in hypertensive patients. This study used a quasi-experimental design with a sample size of 55 respondents with pre-post intervention. The results showed that there were differences in average pain scores between before and after acupressure intervention. Acupressure can be used to reduce pain better with a p value of 0.001. Acupressure therapy has many functions for physical health, one of which is to reduce acute and chronic pain. Pain occurs due to an imbalance of “qi” energy flow in the body. Acupressure will balance the body's “qi” energy flow so that it will relieve pain while curing diseases. This study recommended that health promotion measures be carried out on families and patients so that they can carry out routine blood pressure measurements and alternative treatments with acupressure therapy to reduce complaints due to hypertension.